Pendampingan Do’a Sehari-Hari dalam Pendidikan Aqidah Akhlak terhadap Anak-Anak Majlis Ta’lim Nurul Huda - Farah Afifah Septiani; Wawan Oktriawan; Dede Supendi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Majlis ta'lim Nurul Huda, which is located in Cirangkong village, Cibatu sub-district, Purwakarta district, is one of the ta'lim majlis, the main focus of which is memorizing daily prayers. The method used is a reasoning method by forming classical and muraja'ah groups, submitting prayers one by one to the mu'allimah. The problem faced by majlis children is that some children make memorizing prayers quite a burden. Apart from that, they memorize without knowing the etiquette of praying, its meaning and benefits in everyday life. Therefore, at this majlis ta'lim, service will be carried out in the form of mentoring the children of the majlis ta'lim to increase their knowledge of daily prayers and remember them so that they can be practiced in everyday life. The method used in this service is PAR (Participatory Action Research). Namely, with the stages of observation, data collection, monitoring, action and evaluation. The aim of this method of assistance is to effectively read daily prayers, increase interest in memorizing daily prayers, and find out what daily prayers have potential in the Aqidah and Moral education of the students of the Ta'lim assembly in life. everyday, with more fun. Some of the results of the service carried out are, first; increase knowledge of prayers ranging from short to long, second; understand how to memorize daily prayers easily, and third; understand the benefits and advantages of this prayer. The assistance provided to the children of malis ta'lim Nurul Huda aims to ensure that the children always improve the quality of their daily prayer readings and make deposits not only out of obligation. More than that, they can increase their enthusiasm for memorizing and applying it in everyday life, by knowing the benefits and meaning of memorized prayers written in Arabic and their meanings.